METODE PERHITUNGAN TINGKAT KEBERHASILAN PANEN BROILER BERDASARKAN PERFORMANCE INDEX (PI) PADA GRUP TERNAK DI KOTA PRABUMULIH - Ahmad Sanmorino (Jurnal Informatika Global)
In this study, we tried to propose a method to assess the success of the harvest broiler using internal factors found on farms in Prabumulih. To be able to measure the success rate of harvest broiler, we use the Performance Index (PI) as a parameter. By looking at the results of measuring the degree of success of the crop expected broiler breeder who owns the farm, especially in Prabumulih, can better utilize and maximize the potential that can increase crop yields. After going through a testing phase, the percentage of harvest success rate reached 90% when the results of calculation of the value of PI reached the high category. This proves that by looking at the value of PI, farmers, especially in the farm group in Prabumulih can predict the success rate of harvest in a period. By calculating the value of PI and learn all variables breeders can develop appropriate measures to avoid the occurrence of crop failure. With reference to the value of PI, farmers can also make better planning in preparing the development of broiler chickens for the next period.Key words :success rate, Performance Index, Broiler